Perineal ectopic testis with unilateral scrotal hypoplasia - V. Jafarov (Elsevier, 2019)
Perineal ectopic testis, is one of the least commonly seen abnormalities of testicular descent. Ectopic testis represents approximately one percent of undescended testis cases. Perineum should especially be examined in a case where testicle could not be palpated scrotally. In this study we present a case operated for perineal ectopic testis. The patient was referred to our clinic with a prediagnosis of non-palpabl testis. During physical examination perineal ectopic testis was detected. At the operation perineally located gubernacular tissue was explored and placed to the scrotal cavity together with the testis. Keywords: Perineal ectopic testis, Congenital anomaly, Orchiopexy